2020
DOI: 10.3390/agriculture10080335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inoculation with Preactivated Lactobacillus Buchneri and Urea on Fermentative Profile, Aerobic Stability and Nutritive Value in Corn Silage

Abstract: The current study aimed to evaluate the application effects of the preactivated Lactobacillus buchneri and urea on the fermentative characteristics, chemical composition and aerobic stability in corn silages. The design was completely randomized, in a 6 × 5 factorial arrangement, with six types of additive and five opening times. The treatments consisted of corn silage; corn silage with freeze-dried inoculant; corn silage with freeze-dried inoculant +1.0% urea; corn silage with activated inoculant; corn silage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
2
14
2
Order By: Relevance
“…Butyric acid, as the main product of Clostridium sp., should not be detectable in well-fermented silage (Kung et al, 2018a). In contrast to the present study, Santos et al (2020) observed the presence of butyric acid in all samples of corn silage (0.03-0.04%) along with a positive effect of activated L. buchneri. The different content of formic acid was observed in silage LAB2 in comparison with C (P < 0.05).…”
Section: The Main Fermentation Parameters Of Corn Silagecontrasting
confidence: 99%
“…Butyric acid, as the main product of Clostridium sp., should not be detectable in well-fermented silage (Kung et al, 2018a). In contrast to the present study, Santos et al (2020) observed the presence of butyric acid in all samples of corn silage (0.03-0.04%) along with a positive effect of activated L. buchneri. The different content of formic acid was observed in silage LAB2 in comparison with C (P < 0.05).…”
Section: The Main Fermentation Parameters Of Corn Silagecontrasting
confidence: 99%
“…The AA content of the BS group was significantly higher than that of the CK group, which may account for the better aerobic stability of the BS group ( Basso et al, 2012 ; Bai et al, 2022a ). Acetic acid has good antifungal properties and can inhibit the growth of fungi, thereby inhibiting the process of aerobic spoilage of silage ( Santos et al, 2020 ). There was no significant difference in the number of yeasts among treatments, and the number of filamentous fungi was below the detection limit, because the lower pH maintains an acidic environment and inhibits the growth of yeasts and filamentous fungi ( Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…thereby inhibiting the process of aerobic spoilage of silage (Santos et al, 2020). There was no significant difference in the number of yeasts among treatments, and the number of filamentous fungi was below the detection limit, because the lower pH maintains an acidic environment and inhibits the growth of yeasts and filamentous fungi (Sun et al, 2021).…”
Section: Materials Characteristics and Silage Qualitymentioning
confidence: 96%
“…Apart from T-2 toxin, none of the listed mycotoxins in table 1 exceeded the maximum permitted limit set by the European Union. Several authors paid attention to the effect of urea addition (Santos et al, 2021;Fiantok, 2020;Kaewpila et al, 2020;Santos et al, 2020;Zamir et al, 2020;Santos et al, 2018;Kang et al, 2018;Kebede et al, 2018), but monitored the changes in nutritional…”
Section: Resultsmentioning
confidence: 99%